Detection and prevalence of Capnocytophaga in periodontal Health and disease - Pushpa S Pudakalkatti; Abhinav S Baheti; Sanjeevini A Hattarki; Soumya S Kambali; Reshma M Naik (Wolters Kluwer Medknow Publications, 2016)
Context/Background: Periodontal disease is a multifactorial disease, in which bacteria play a major role. Capnocytophaga species form a part of human oral flora both in health and disease. They have been implicated as putative periodontal pathogens, and yet, they are less understood members of plaque flora. No studies have been conducted on the association of Capnocytophaga species with periodontal diseases in India. Aim: The aim of this study was to detect the prevalence of Capnocytophaga species in patients with healthy periodontium, gingivitis, and periodontitis using culture method. Methods: Forty patients each with healthy periodontium, gingivitis, and periodontitis were selected. Subgingival plaque samples were collected from all the patients using sterile curettes and transferred to transport medium and sent to the laboratory. The plaque samples were inoculated on blood agar and trypticase-blood-bacitracin-polymyxin agar to grow Capnocytophaga species. Later, Gram-staining and microscopy were done to confirm the presence of Capnocytophaga in each sample. The prevalence of Capnocytophaga species was statistically analyzed using Chi-square test, Kruskal-Wallis analysis of variance, and Mann-Whitney U-test. Results: Capnocytophaga was detected in 21 (52.50%) samples out of 40 samples of gingivitis group, 11 (27.50%) samples of healthy group, and 12 (30%) samples of periodontitis group. Conclusions: Capnocytophaga is more prevalent in gingivitis compared to healthy periodontium and periodontitis. Capnocytophaga has the potential to cause periodontal disease, but as it is less competitive in the periodontal pocket, it is usually overgrown by other rapidly growing bacteria.